The NEDD4/FLRT2 axis regulates NSCLC cell stemness - Yang, Yuping; Yan, Fei; Gao, Ziwei; Li, Houke; Wen, Shengke; Li, Qi; Li, Jiayuan; Huang, Na; Zhao, Wei (Frontiers in Pharmacology, 2024)
Lung cancer is the leading cause of cancer-related death worldwide. The treatment for lung cancer, particularly for non-small cell lung cancer (NSCLC), remains a clinical challenge. Cancer stem cells are vital for lung cancer development. This study aimed to determine the influence of the neuronally expressed developmentally downregulated 4-fibronectin leucine-rich transmembrane 2 (NEDD4-FLRT2) axis on cancer cell stemness in NSCLC. Here, we reported that FLRT2 expression was reduced in NSCLC tissues, cells, and NSCLC stem cells. FLRT2 upregulation inhibited NSCLC stem cell proliferation, sphere formation, and drug resistance and promoted drug-resistant cell apoptosis. Furthermore, FLRT2 overexpression demonstrated antitumor effects in a xenograft tumor mouse model. Mechanically, FLRT2 was ubiquitinated and degraded by E3 ligase NEDD4. NEDD4 overexpression significantly abolished the inhibitory effects of FLRT2 on NSCLC stemness, as evidenced by in vitro and in vivo experiments. This study revealed that FLRT2 acted as a tumor suppressor by inhibiting cancer cell stemness in NSCLC. NEDD4 promoted ubiquitination degradation of FLRT2 protein. NEDD4 counteracted the inhibitory effects of FLRT2 on NSCLC stem cell tumorigenesis.